Response of Tuber melanosporum fruiting to canopy opening in a Pinus-Quercus forest - Garcia-Barreda, Sergi; Reyna, Santiago (ECOLOGICAL ENGINEERING, 2013)
The wild production of the highly appreciated fungus Tuber melanosporum is negatively affected by canopy closure in the stand. Habitat improvement has been proposed as a tool to recover the production in close forests, but evaluations based on scientific monitoring are still lacking. This study analyses the short-term effect of a pilot project on improvement of T. melanosporum reproduction habitat. The results support the project hypothesis that the canopy closure was hampering truffle fruiting in the larger brines. The silvicultural treatment alone has not triggered a clear positive response in all the truffieres, suggesting that complementary actions are necessary to ensure their sustainability. Weather conditions provoke a year-to-year variation in the fruiting and determine the responsiveness of the truffieres to the treatment. (C) 2012 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: Canopy closure; Non-wood forest products; Quercus ilex; silviculture; Tuber melanosporum